18F-FDG-PET Detects Drastic Changes in Brain Metabolism in the Tg4–42 Model of Alzheimer’s Disease - Bouter, Caroline; Henniges, Philipp; Franke, Timon N.; Irwin, Caroline; Sahlmann, Carsten Oliver; Sichler, Marius E.; Beindorff, Nicola; Bayer, Thomas A.; Bouter, Yvonne (Frontiers in Aging Neuroscience, 2019)
The evaluation of new therapeutic strategies in Alzheimer’s disease (AD) relies heavily on in vivo imaging and suitable animal models that mimic the pathological changes seen in patients. 18F-Fluorodeoxyglucose (18F-FDG)-positron-emission tomography (PET) is a well-established non-invasive imaging tool for monitoring changes in cerebral brain glucose metabolism in vivo. 18F-FDG-PET is used as a functional biomarker for AD as patients show an early and progressive reduction of cerebral glucose metabolism. However, earlier studies in preclinical models of AD showed conflicting results. The aim of this study was the evaluation of cerebral glucose metabolism in the Tg4–42 mouse model of AD using 18F-FDG-PET/magnetic resonance imaging (MRI). Tg4–42 mice show an age-dependent reduction in glucose metabolism together with severe neuron loss and memory deficits. Similar to AD patients early decrease in 18F-FDG uptake was already detected in young (3 months) Tg4–42 mice. The altered glucose metabolism coupled with age- and disease related cognitive decline of Tg4–42 mice make it a well-suited model for preclinical testing of AD-relevant therapeutics.